1978
DOI: 10.1099/00207713-28-4-582
|View full text |Cite
|
Sign up to set email alerts
|

Pectinatus, a New Genus of the Family Bacteroidaceae

Abstract: The properties of an anaerobic, rod-shaped bacterium having an unusual flagellar arrangement are described. The flagella emanate from only one side of the cell body and are not limited to the center portion as they are with selenomonads. The organism is a gramnegative, nonsporeforming mesophile producing acetic, propionic, and succinic acids and traces of lactic acid from glucose fermentation. The guanine-plus-cytosine content of the deoxyribonuleic acid is 39.8 mol%. The characteristics of this organism indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
2
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 3 publications
7
88
2
1
Order By: Relevance
“…Pectinatus cerevisiiphilus was first described by Lee et al 109 Currently, Pectinatus species have been implicated in 20-30% of bacterial spoilage incidents encountered in finished product, usually in non-pasteurised rather than pasteurised beers 5 . The natural habitats and sources of the Pectinatus spp.…”
Section: Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pectinatus cerevisiiphilus was first described by Lee et al 109 Currently, Pectinatus species have been implicated in 20-30% of bacterial spoilage incidents encountered in finished product, usually in non-pasteurised rather than pasteurised beers 5 . The natural habitats and sources of the Pectinatus spp.…”
Section: Fermentationmentioning
confidence: 99%
“…Beer spoilage by Pectinatus spp. is characterised by extensive turbidity and an offensive 'rotten egg' smell as a result of the production of hydrogen sulphide and methyl mercaptan 72,109,110 .…”
Section: Fermentationmentioning
confidence: 99%
“…Strain Nor1 T differs from Thermanaerovibrio species by the ability to grow chemolithotrophically on CO, producing H 2 and CO 2 , and the phylogenetic distance between Nor1 T strain and Thermanaerovibrio species. A phylogenetic analysis revealed that strain Nor1 T adds to the list of bacterial genera that show Gram-negative-type cell walls but belong to the phylogenetic lineage of Gram-positive bacteria (Lee et al, 1978). By similarity percentage, the closest relative appears to be D. quercicolus (Strömpl et al, 2000).…”
Section: S Rrna Gene Sequence Analysismentioning
confidence: 99%
“…Pectinatus was reported as a new genus of Gram negative, catalase negative, motile, obligate beer spoilage bacteria in the 1970s, when it was first isolated from a brewery in the United States in unpasteurized beer stored at 30°C 31 . P. cerevisiiphilus was later isolated from breweries in Finland, Germany, Norway, Japan, Spain, Netherlands, Sweden and France 15,29,45,50 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, a third species, Pectinatus haikarae was identified on the basis of 16S rRNA gene sequence analysis and differences in sugar utilization, catalase activity, antibiotic resistance and temperature tolerance compared to the two previously characterised 25 . The growth of Pectinatus species is accompanied by extensive turbidity and an offensive aroma similar to rotten egg due to the production of various fatty acids, hydrogen sulphide and methyl mercaptan 15,31 .…”
Section: Introductionmentioning
confidence: 99%